Living near opencast coal mining sites and children's respiratory health. Issue 3 (1st March 2000) - Pless-Mulloli, Tanja; Howel, Denise; King, Andrew; Stone, Ian; Merefield, John; Bessell, Jan; Darnell, Ross
Abstract : OBJECTIVES: To answer the question whether living near opencast coal mining sites affects acute and chronic respiratory health. METHODS: All 4860 children aged 1–11 from five socioeconomically matched pairs of communities close to active opencast sites and control sites away from them were selected. Exposure was assessed by concentrations of particulate matter with aerodynamic diameter <10 μm (PM10 ), residential proximity to active opencast sites, and particle composition. PM10 was monitored and sampled for 6 weeks in four pairs, and for 24 weeks in one pair. A postal questionnaire collected data on health and lifestyle. Daily health information was collected by a symptom diary (concurrently with PM10 monitoring) and general practitioner (GP) records were abstracted (concurrently with PM10 monitoring and 52 weeks before the study). Outcomes were the cumulative and period prevalence (2 and 12 months) of wheeze, asthma, bronchitis, and other respiratory symptoms, and the prevalence and incidence of daily symptoms and GP consultations. RESULTS: Patterns of the daily variation of PM10 were similar in opencast and control communities, but PM10 was higher in opencast areas (mean ratio 1.14, 95% confidence interval (95% CI) 1.13 to 1.16, geometric mean 17.0 μg/m 3 v 14.9 μg/m 3 ). Opencast sites were a measurable contributor to PM10 in adjacent areas. Little evidence was found for associations between living near an opencast site and an increased prevalence of respiratory illnesses, asthma severity, or daily diary symptoms, but children in opencast communities 1–4 had significantly more respiratory consultations (1.5 v 1.1 per person-year) than children in control communities for the 6 week study periods. Associations between daily PM10 concentrations and acute health events were similar in opencast and control communities. CONCLUSIONS: Children in opencast communities were exposed to a small but significant amount of additional PM10 to which the opencast sites were a measurable contributor. Past and present respiratory health of children was similar, but GP consultations for respiratory conditions were higher in opencast communities during the core study period.